ANALISIS YURIDIS TERHADAP SURAT KEPUTUSAN BERSAMA MENTERI (Studi pada Surat Keputusan Menteri Dalam Negeri, Menteri Pendayagunaan Aparatur Negara dan Reformasi & Birokrasi serta Kepala Badan Kepegawaian Negara No.128/6597/Sj, No.15 Tahun 2018, No.153/Kep/2018 - I gusti ngurah made sumantri; I Wayan Gde Wiryawan (Jurnal Hukum Mahasiswa, 2023)
This Joint Decree (SKB) of 3 Ministers is a product of the government and serves as a guideline for officials authorized to issue punishments to issue decisions on honorable or dishonorable dismissal for civil servants who have committed a crime. Therefore, the author is interested in formulating the following problems: (1) how is the juridical study of the Joint Ministerial Decree on Law Enforcement Against Civil Servants Who Have Been Sentenced to Based on a Court Decision with Permanent Legal Force for Committing a Crime of Occupational Crime in Freies Ermessen against Civil Servants in the Provincial Government of Bali, (2) how is the validity of the Joint Ministerial Decree in imposing sentences based on Court Decisions with Permanent Legal Force for Committing a Crime of Occupational Crime. The results of the study: (1) Juridical study of the Ministerial Joint Decree on Law Enforcement Against Civil Servants Who Have Been Sentenced to a Court Decision with Permanent Legal Force for Committing a Crime Act in the freies emerssen against Civil Servants in the Provincial Government of Bali will lead to ambiguity in the form of state administrative legal actions which can lead to conflict norms between these SKB 3 Ministers and Law Number 5 of 2014 concerning State Civil Apparatuses which in this case is the giver of authority to be able to see from the validity of the Ministerial Joint Decree, (2) The validity of the Joint Decree of the 3 Ministers can be concluded: first, this SKB of 3 Ministers is a policy regulation issued as a guideline for Personnel Development Officials based on a court decision that has permanent legal force. Second, the SKB 3 Ministers can be qualified as a legal juridical instrument (rechtmatig), unless it is enforced backwards (terugwerkend).